Effects of preoperative celecoxib administration on pain control after tibial fracture surgery: A randomized controlled trial - Abtahi, Dariush (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: We hypothesized that preoperative different doses of celecoxib would reduce pain scores and morphine consumption after tibial fracture surgery under spinal anesthesia. Materials and Methods: In this randomized, double-blind, controlled study of 484 subjects undergoing tibial surgery, patients received a placebo (Group O) or celecoxib (Group A: 100 mg, Group B: 200 mg, Group C: 400 mg) one hour before surgery. The primary endpoint was pain severity in the recovery room at 6, 18, and 24 hours postoperatively. The secondary endpoints were postoperative nausea and vomiting (PONV), agitation in the recovery room, total opioid use, and time to the patient’s first request for analgesics. Results: Compared to the placebo group, the celecoxib groups had significantly lower postoperative pain scores (p<0.001). They also had significantly lower PONV (P-value<0.05), agitation in the recovery room (P-value=0.001), and a longer time to request analgesics (P-value<0.05). The difference within the celecoxib groups was almost insignificant. The difference between the groups for total opioid use was not significant (p>0.05). Conclusions: Administration of celecoxib before tibial fracture surgery under spinal anesthesia was associated with significantly reduced early VAS pain scores, PONV, agitation in the recovery room, and delayed time to initiation of postoperative analgesic use, but not for total opioid use. We recommend premedication with low-dose (100 mg) celecoxib for the above purposes.